The role of cGAS-STING pathway ubiquitination in innate immunity and multiple diseases - Deng, Chunyan; Chen, Dongyan; Yang, Liang; Zhang, Yubiao; Jin, Cheng; Li, Yue; Lin, Qihong; Luo, Mingjing; Zheng, Ruihao; Huang, Baozhen; Liu, Sixi (Frontiers in Immunology, 2025)
The cGAS-STING pathway is essential in innate immunity, especially in antiviral responses and cellular stress management. cGAS acts as a cytoplasmic DNA sensor by initiating the synthesis of the second messenger cyclic GMP-AMP synthase (cGAMP), which subsequently activates the STING pathway, leading to the production of type I interferons and other cytokines, as well as the activation of inflammatory mediators. Recent studies have demonstrated that ubiquitination changes closely regulate the function of the cGAS-STING pathway. Ubiquitination modifications influence the stability and activity of cGAS and STING, while also influencing the accuracy of the immune response by adjusting their degradation and signal intensity. E3 ubiquitin ligase specifically facilitates the degradation or modulates the signaling of cGAS-STING-associated proteins via ubiquitination alterations. Furthermore, the ubiquitination of the cGAS-STING pathway serves distinct functions in various cell types and engages with NF-κB, IRF3/7, autophagy, and endoplasmic reticulum stress. This ubiquitin-mediated regulation is crucial for sustaining the balance of innate immunity, while excessive or inadequate ubiquitination can result in autoimmune disorders, cancers, and viral infections. An extensive examination of the ubiquitination process within the cGAS-STING pathway elucidates its specific regulatory mechanisms in innate immunity and identifies novel targets for the intervention of associated diseases.